Stable Boron Dithiolene Radicals. (22nd May 2018) - Wang, Yuzhong; Xie, Yaoming; Wei, Pingrong; Blair, Soshawn A.; Cui, Dongtao; Johnson, Michael K.; Schaefer, Henry F.; Robinson, Gregory H.
Abstract: Whereas low‐temperature (−78 °C) reaction of the lithium dithiolene radical1 . with boron bromide gives the dibromoboron dithiolene radical2 ., the parallel reaction of1 . with (C6 H11 )2 BCl (0 °C) affords the dicyclohexylboron dithiolene radical3 . . Radicals2 . and3 . were characterized by single‐crystal X‐ray diffraction, UV/Vis, and EPR spectroscopy. The nature of these radicals was also probed computationally. Under mild conditions, 3 . undergoes unexpected thiourea‐mediated B−C bond activation to give zwitterion4, which may be regarded as an anionic dithiolene‐modified carbene complex of the sulfenyl cation RS + (R=cyclohexyl).